The Role of Social Media in Supporting Information and Intelligence Gathering by Densus 88 - Virgantara, Aliviqo Pandu; Nita, Surya; Rahmanto, Didik Novi (Security Intelligence Terrorism Journal (SITJ), 2024)
Terrorism in the digital era has rapidly evolved, with terrorist groups increasingly utilizing social media platforms to spread radical ideologies, recruit new members, and plan attacks. Indonesia, having experienced various terrorism incidents, continues to face this ongoing threat. In this context, the Special Detachment 88 Anti-Terrorism Unit (Densus 88) leverages social media as a critical tool for intelligence gathering and preventing terrorist activities. This study aims to explore how Densus 88 utilizes platforms such as Facebook, Twitter, Instagram, and YouTube to identify, monitor, and analyze terrorism-related activities. Through a qualitative approach, this research investigates the perspectives and experiences of Densus 88 members involved in using social media as an intelligence tool. The findings indicate that social media provides a continuous data stream that can be used to monitor activities, track trends, and identify potential threats at an early stage. However, significant challenges remain, including the vast volume and complexity of data and difficulties in distinguishing genuinely dangerous activities from unrelated content. This study provides valuable insights into the strategic use of social media in counter-terrorism operations and suggests measures to enhance the effectiveness of intelligence gathering in the digital era.